1996
DOI: 10.1002/actp.1996.010470103
|View full text |Cite
|
Sign up to set email alerts
|

Uniform polymer beads of micrometer size

Abstract: Various methods are reviewed that have been developed in recent years to produce uniform polymer beads with diameter larger than 1 pm. Methods such as emulsifier-free emulsion polymerization, suspension polymerization (including non-standard polymerization devices and a method of activated swelling), dispersion polymerization, precipitation polymerization, and other techniques are covered. The discussion focuses on the mechanism of bead formation and variables influencing the properties of the beads. Potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 79 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…Instead, the suggested particle formation process is based on a rapid coagulation process preceded by a short nucleation period. This could also explain the narrow size distribution of the MPTMS organosilica particles [41,42].…”
Section: Resultsmentioning
confidence: 95%
“…Instead, the suggested particle formation process is based on a rapid coagulation process preceded by a short nucleation period. This could also explain the narrow size distribution of the MPTMS organosilica particles [41,42].…”
Section: Resultsmentioning
confidence: 95%
“…[4] Very systematic and detailed studies have also been reported by Taylor and Dawkins, [193] Horák, [194] and Croucher and Winnik. [195] Without going into details of the kinetics and thermodynamics of this polymerization process, which has been reviewed by the previously mentioned authors, in the following we intend to provide some more recent examples of NAD prepared in the presence of block copolymers as a stabilizer either by free radical or ionic polymerization as well as by polycondensation reactions.…”
Section: Dispersion Polymerization In Organic Solventsmentioning
confidence: 93%
“…A review covering the state of the art with regard to synthesis and application until the mid-1990s can be found in [157].…”
Section: Some Practical Examples ± Monodisperse Latexesmentioning
confidence: 99%